Critical genres and radical criminology in Britain - Pavlich, George (The British journal of criminology, 2001)
Analyses highlighting the genres of critique engaged by radical criminologists are comparatively rare. The few exceptions tend to associate radical criminological thinking with a grammar of critique that (i) establishes universal criteria, (ii) judges (con)texts against these and (iii) prescribes paths of action accordingly. This is an unfortunate tendency since it ties radical thought to an increasingly anachronistic genre of critique, and does not arrest the dwindling plight of critical approaches, or resist dominant technocratic discourses in criminology. In an attempt at redress, this paper identifies four alternate genres of critique in British radical criminology of the 1960s-70s, and shows how these could spawn a deconstructive ethos from which to develop critical analysis with renewed legitimacy